The marine cartilaginous fishes and sturgeons of the Sea of Marmara: an updated and annotated checklist - Artüz, M. Levent; Fricke, Ronald (Zootaxa, 2024)
A revised checklist of sharks, batoids, and sturgeons in the Sea of Marmara, Turkey encompasses 41 species across 18 families. It provides a concise historical context and addresses issues related to problematic reports. Furthermore, the paper delves into the analysis of taxonomic changes in other literature reports, aiming to provide a framework for upcoming ichthyological surveys and ecological studies, while also presenting relevant data on the economic significance of select species.